FDI in Sub Saharan Africa - BEKELLE, Engida Abebe (KDI School, 2018)
The growth process of the Sub Saharan Africa region has not been significantly influenced by Foreign direct investment inflow in the previous 25 years. The robustness of the result is tested using various model specifications. First pooled OLS regression method was applied; however, due to its methodological limitations of not removing the biasedness of the results, the result was not accepted. Therefore, to control for at least the unobservable time invariant variables, panel fixed effect model was used. Using this method was not sound enough to remove all biasedness of the estimates. Thus, to get the most efficient estimates two strategies were employed: first, three stages least square (TSLS) combined with fixed effect was used with similar insignificant results; and Finally, an instrumental variable approach using investment freedom as an instrument for FDI is used resulting in high positive impact compared to other models; although it was insignificant. In addition, the main constraining factors of FDI inflow in to the sub region were unbundled. The study found that improvement in investment freedom has played a positive significant role. the other categories of variables such as resource endowment, macro-economic related policies, human right, human capital and institutional variables did not have a meaning full effect on the FDI inflow. The paper used various methodologies including fixed effect and TSLS to control for all the sources of the endogeneity.
Thesis(Master) --KDI School:Master of Development Policy,2018